Ultrastructural changes of the peritoneum in a rabbit model of peritoneal dialysis - Jovanović, Nataša; Žunić-Božinovski, Snežana; Trpinac, Dušan; Laušević, Željko; Krstić, Slobodan; Oprić, Dejan; Trbojević-Stanković, Jasna; Stojimirović, Biljana (Vojnosanitetski pregled, 2017)
Background/Aim. The number of patients with end-stage renal diseases treated with chronic dialysis is increasing over the last years. Long-term peritoneal dialysis is associated with progressive development of structural and functional alterations of peritoneal membrane. The aim of the study was to analyze ultrastructural alterations of mesothelial monolayer and submesothelial tissue in a modified non-uremic experimental model of peritoneal dialysis in rabbits. Methods. The study was performed on 5 healthy Chinchilla rabbits. Surgical procedures of implantation and removal of peritoneal catheter, prevention of catheter clothing, prevention of infection and dialysate instillation were performed according to previously described protocols. Peritoneal tissue samples were collected upon catheter placement and removal after a 5-week follow-up and processed for transmission electron microscopy (TEM) examination. Results. The rabbits tolerated anesthesia, surgical procedure and the applied regimen of dialysate instillations well. The animals recovered completely and no adverse effects were noted. In the animals treated with peritoneal dialysis instillations, TEM revealed alterations of the mesothelial monolayer and submesothelial tissue. The mesothelial cells in direct contact with dialysis fluid were prone to shrinking. They lost the typical cobblestone morphology and assumed a flattened shape. The mesothelial cells were often detached from the basement membrane. These cells showed euchromatic nuclei, higher number of microvilli in their apical part and very numerous vesicles. A higher quantity of collagen fibers was noticed in the peritoneal lamina propria in close relation to the basement membrane of mesothelium. The nuclei of the fibroblasts were also euchromatic. Numerous mitochondria, granules and vesicles were present in their cytoplasm. Conclusion. The used rabbit model of peritoneal dialysis is simple, practical to perform, reproducible, not expensive and not requiring advanced devices. It is suitable for obtaining peritoneal tissue samples for histological examination and can be used to analyze the effects of dialysis solutions on the rabbit peritoneal membrane.